Coping Strategies and Suicidality: A Cross-Sectional Study From China - Liang, Jianqiang; Kõlves, Kairi; Lew, Bob; de Leo, Diego; Yuan, Lu; Abu Talib, Mansor; Jia, Cun-xian (Frontiers in Psychiatry, 2020)
Background and objective: Suicide is a leading cause of death in young people. Suicidal thoughts and behaviors can be triggered by life and study stresses; therefore it is important to understand the role of coping strategies. The current study analyzed the link between different coping strategies and suicidality in university students in China. Methods: A cross-sectional study of 2,074 undergraduate students from China used a stratified-clustered-random sampling method (response rate 94.4%). The Suicidal Behaviors Questionnaire-Revised Scale was used to identify suicidal risks, while the Brief COPE scale was used to measure different coping strategies. Univariate and multivariate logistic regression analyses were utilized to examine coping strategies and suicidality. Results: A negative association of some coping skills (active coping and positive reframing) with suicidality, and a positive association of some other coping skills (self-distraction, substance abuse, behavioral disengagement, venting and self-blame) with suicidality was observed after adjusting for socio-demographic and mental health variables. Conclusions: Training and supporting young people to identify and apply adaptive coping strategies to deal with life stress could help to reduce suicidal ideation and behavior.